Isobutrin from butea monosperma (flame of the forest): a promising new natural sensitizer belonging to chalcone class - Agarkar, Shruti A.; Kulkarni, Roshan R.; Dhas, Vivek V.; Chinchansure, Ashish A.; Hazra, Partha; Joshi, Swati P.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2011)
In this work, ``isobutrin'', an ecofriendly sensitizer that is extracted from Butea monosperma (commonly known as ``Flame of the Forest'') flowers, is introduced. It is a bright yellow pigment belonging to the chalcone class and is examined as a sensitizer for optoelectronic applications. It is observed that chelation of this dye with Ti ions results into a strong dye-TiO(2) charge transfer (DTCT) band in the visible region. This Ti-Isobutrin chelate is stable, irreversible and its formation is studied using Benesi-Hildebrand plot. The locations of HOMO-LUMO states of the Ti-isobutrin chelate and the corresponding band alignment with TiO(2) are obtained. Also, a thermal stability test revealed that isobutrin is stable above 100 degrees C.
Keywords: Butea monosperma; chalcone; dye-sensitized solar cell; isobutrin; sensitizer; TiO(2)

Pt- and TCO-free flexible cathode for DSSC from highly conducting and flexible PEDOT paper prepared via in situ interfacial polymerization - Anothumakkool, Bihag; Agrawal, Ishita; Bhange, Siddheshwar N.; Soni, Roby; Game, Onkar S.; Ogale, Satishchandra B.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2016)
Here, we report the preparation of a flexible, free-standing, Pt- and TCO-free counter electrode in dye-sensitized solar cell (DSSC)-derived from polyethylenedioxythiophene (PEDOT)-impregnated cellulose paper. The synthetic strategy of making the thin flexible PEDOT paper is simple and scalable, which can be achieved via in situ polymerization all through a roll coating technique. The very low sheet resistance (4 Omega/square) obtained from a film of 40 mu m thick PEDOT paper (PEDOT-p-5) is found to be superior to the conventional fluorine-doped tin oxide (FTO) substrate. The high conductivity (357 S/cm) displayed by PEDOT-p-5 is observed to be stable under ambient conditions as well as flexible and bending conditions. With all of these features in place, we could develop an efficient Pt- and TCO-free flexible counter electrode from PEDOT-p-5 for DSSC applications. The catalytic activity toward the tri-iodide reduction of the flexible electrode is analyzed by adopting various electrochemical methodologies. PEDOT-p-5 is found to display higher exchange current density (7.12 mA/cm(2)) and low charge transfer resistance (4.6 Omega) compared to the benchmark Pt-coated FTO glass (2.40 mA/cm(2) and 9.4 Omega, respectively). Further, a DSSC fabricated using PEDOT-p-5 as the counter electrode displays a comparable efficiency of 6.1% relative to 6.9% delivered by a system based on Pt/FTO as the counter electrode.
Keywords: counter electrode; dye-sensitized solar cell; flexible and thin devices; impedance analysis; interfacial polymerization; polyethylenedioxythiophene

Interplay between pi-bridges and positions of branched alkyl groups of unsymmetrical D-A-D-pi-A squaraines in dye-sensitized solar cells: mode of dye anchoring and the charge transfer process at the TiO2/Dye/electrolyte interface - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2017)
Far-red-absorbing squaraines possessing high molar absorptivity (>10(5) M-1 cm(-1)) are being attracted as high-efficiency chromophores in dye-sensitized solar cells (DSSCs). A series of donor acceptor -donor-pi spacer-acceptor (D-A-D-pi-A) unsymmetrical squaraines, PSQ1-5, with indoline donor and squaric/cyanoacetic acid acceptor units, were designed for sensitized solar cells. For extending the absorption toward the near-infrared region (NIR) and controlling the orientation on the TiO2 surface, benzene (PSQ1 and PSQ2) and thiophene (PSQ3-5) 7r-spacers and out-of-plane branched alkyl groups at the indoline that are away (PSQ1, PSQ3, and PSQS) or near (PSQ2 and PSQ4) the anchoring group, respectively, were introduced. Dynamic aggregation tendency of PSQ1 and PSQ3 than that of their isomers systematically modulates the orientation on the TiO2 surface, which in turn enhances photovoltaic performance. Absorptance on a thin transparent TiO2 film shows a visible-to-NIR response with an onset around 800 nm for PSQ3-5. Although there is resemblance in electrochemical redox levels, their high injection efficiency and recombination resistance differentiated impact on the way of anchoring and the dihedral angle between D-A-D units and g-spacers. DSSCs sensitized with PSQS achieved a PCE of 8.15% under simulated AM 1.5G illumination (100 mW cm(-2)), with the current density (j) and open-circuit voltage (Voc) of 19.73 mA cm(-2) and 630 mV, respectively. A clear comparison of the incident-photon-to-current conversion efficiency versus the light-harvesting efficiency correlates the structure-property relationship with J obtained for PSQ dyes. Electrochemical impedance spectroscopy was carried out to examine the TiO2/dye/electrolyte interface for further confirmation of the enhanced PCE of top-se-alkylated PSQS over that of other dyes.
Keywords: D-A-D-pi-A framework; dye-sensitized solar cell; H- and J-type aggregation; orientation of dyes; static/dynamic aggregates; unsymmetrical squaraine

Effect and position of spiro-bipropylenedioxythiophene pi-spacer in donor-pi-spacer-acceptor dyes for dye-sensitized solar cell - Sil, Manik Chandra; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Dyes and Pigments, 2019)
Improper orientation and self-assembly of dyes on TiO2 surface are the main disadvantages at the dye-TiO2 interface that governs both charge injection and dye regeneration processes. In this report, a series of homo spiro-dimeric donor-pi-spacer-acceptor (D-pi-A) dyes based on bithiophene and terthiophene spacers with two-anchoring group containing dyes, TT1, T1T, TT1T were designed and synthesized by Pd-catalyzed successive Suzuki coupling followed by direct arylation reactions. The position of branching centre in TT1 and T1T was systematically varied, where the spiro unit was placed near and away from the anchoring carboxylic acid unit, respectively. The dimeric spiro-dye T1T showed device performance, which is 1.6 fold higher than its structural isomeric analogue TT1, of 3.9% with a V-oc and J(sc) of 0.593 V and 9.09 mA/cm2, respectively, whereas for the isomeric analogue TT1 a device performance of 2.45% (V-oc of 0.568 V and J(sc) of 6.25 mA/cm2) under simulated 1 Sun (100 mW/cm2) condition. The improved Voc for the dye T1T compared to TT1 dye was ascribed to the dipole moment exerted by the dyes on TiO2 surface. Further the PCE of 4.16% (V-oc 0.589 V, J(sc) 9.79 mA/cm2 respectively) maximum was observed, when an extra thiophene unit was inserted in between the donor and pi-spacer in dye TT1T. The shifting the position of branching spiroBiProDOT pi-spacer makes an impact on the device performance by synergistically enhancing both Voc and Jsc.
Keywords: CDCA; D-pi-A Spiro dye; Dye aggregation; dye-sensitized solar cell; spiroBiProDOT spacer

Aniline and indoline donors based far-red active unsymmetrical squaraine dyes for dye sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemphotochem, 2024)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on the metal-oxide surface by appending the alkyl groups around the donor or pi-spacer unit of the dye is a potential approach to enhance DSSC efficiency. Further, rigidification of the dye structures by cyclization modulates the photophysical properties of the sensitizer. Here a series of donor-acceptor-donor (D-A-D) type far-red active unsymmetrical squaraine dyes (SQA) have been designed and synthesized, where N,N-dimethylaniline, methylated- and branched-indoline have been used as donor units. These dyes showed absorption between 629-654 nm (lambda max) with the molar extinction coefficient of 1.49-1.94x105 M-1 cm-1. Systematic enhancements in DSSC device efficiency have been observed due to the cyclization and alkyl-groups incorporation in this set of dyes which were further enhanced with the addition of chenodeoxycholic acid (CDCA). The highest DSSC device efficiency of 4.78 % (Jsc of 8.77 mA/cm2 and Voc of 692 mV) has been achieved for SQA3. The IPCE profile of SQA dyes indicates the contribution of aggregated structures for the photocurrent generation. Further, co-sensitization of SQA3 dye with a complementary visible light active dye AK4 showed the enhanced device efficiency of 6.27 % with panchromatic IPCE response. Dye rigidification, and controlled aggregation of dyes on TiO2 by means of cyclization of donor unit and introducing the alkyl groups in the dye structure synergistically improve the dye-sensitized solar cell (DSSC) device performance. Donor-Acceptor-Donor (D-A-D) based unsymmetrical squaraine dye SQA3 showed the DSSC device performance of 4.78 %.image
Keywords: co-sensitization; dye-sensitized solar cell; effect of alkyl chain; molecular planarity; squaraine dye

Far-red active unsymmetrical squaraine dyes containing N-arylated indoline donors for dye sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Jayaraj, Nithyanandhan (Photochemistry and Photobiology, 2024)
Squaraine dyes possess sharp far-red active transition with high extinction coefficient and form aggregates on TiO2 surface. Aggregation of dyes on TiO2 has been considered as a detrimental factor for DSSC device performance, which can be controlled by appending alkyl groups to the dye structures. Hence by integrating alkylated (alkyl groups with both in-plane and out-of-plane) aryl group with indoline moiety to make it compatible with other electrolytes and for controlling the dye-aggregation, a series of squaraine acceptor-based dyes SQA4-6 have been designed and synthesized. SQA4-6 dyes showed absorption between 642 and 653 nm (lambda max), photophysical and electrochemical studies indicated that the HOMO energy levels of this sets of dyes are well aligned with the potentials of I-/I3-\$\$ {\textbackslashmathrm{I}}_3<\^>{-} \$\$ and [Co(bpy)3]2+/3+ redox shuttles for better dye regeneration process. DSSC device efficiency of 3% has been achieved for SQA5 dye with iodolyte (I-/I3-\$\$ {\textbackslashmathrm{I}}_3<\^>{-} \$\$) electrolyte in the presence of 0.3 mM of chenodeoxycholic acid (CDCA). The IPCE profile of DSSC device fabricated with SQA4-6 dyes indicated the contribution of aggregated structures for the photocurrent generation. Dye-sensitized solar cell (DSSC) device efficiency of 3% (Jsc 5.72 mA cm-2, Voc 662 mV and ff 79%) has been achieved for an unsymmetrical squaraine dye, SQA5 with iodolyte electrolyte and the incident photon to current efficiency (IPCE) profile indicates the contribution of aggregated structures for the photocurrent generation.*image
Keywords: aggregation of dye; arylation on N-atom of indoline donor; dye-sensitized solar cell; squaraine dye

Far-red active squaraine dye-sensitized photoanode for dye-sensitized solar cells with a copper (II/I) electrolyte - Nawghare, Indrajeet S.; Deshmukh, Shivdeep Suresh; Joshi, Krati; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on TiO2 and charge recombination between electrons present in TiO2 and electrolyte can be achieved by wrapping the long alkyl groups around the dye structure and further introducing bulky donor on the dye is a potential approach to enhance both the open-circuit potential and short-circuit current parameters. Additionally, bulky donor containing dye structures modulates the photophysical and electrochemical properties of the sensitizer which helps reducing the over potentials required for the dye regeneration process by utilizing a multidentate ligand containing [Cu(tme)]2+/+ and I- /I3redox electrolytes. Hagfeldt donor appended far-red NIR active unsymmetrical squaraine dye (SQ-HF) has been designed, synthesized, and characterized. SQ-HF dye showed an intense absorption at 676 nm (epsilon 1.7 x 105 M- 1cm- 1). Photophysical and electrochemical studies indicated that the LUMO and HOMO energy levels of the SQ-HF dye were suited for charge injection (from the LUMO of the dye to the conduction band of TiO2) and dyeregeneration processes, respectively. The DSSC device efficiency of 5.15 % (JSC of 10.83 mA/cm2 and VOC of 0.690 V) has been achieved for SQ-HF dye by utilizing a literature reported [Cu(tme)]2+/+ and 4.11 % (JSC of 8.74 mA/cm2 and VOC of 0.702 V) in I- /I3- redox shuttles, respectively.
Keywords: aggregation of dyes; Bulky donor; dye-sensitized solar cell; Photocurrent generation; squaraine dye